2013
DOI: 10.1007/s11274-013-1460-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bacterial communities of biofilms formed on different membrane surfaces

Abstract: Bacterial biofilm communities formed on different membrane surfaces were investigated based on 16S rRNA gene sequence analysis. The biofilm communities were distinct from those of mixed-liquor and consisted mainly of Beta- and Gammaproteobacteria. Sequences of Xathomonas and Aquabacterium were mostly retrieved from the biofilm samples rather than from the mixed liquor. Furthermore, statistical analyses demonstrated the importance of a physico-chemical property of membrane, surface roughness, in structuring the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 13 publications
1
13
0
1
Order By: Relevance
“…This difference was due to the difference in the assembly mechanism of AS and biofilm communities, which are two distinct forms of microbial aggregates. Similar results were reported in previous studies where the biofilm community was distinct from the AS community in lab- (Lim et al, 2004;Choi et al, 2006;Zhang et al, 2006;Huang et al, 2008;Fontanos et al, 2010;Lim et al, 2012;Piasecka et al, 2012;Lee et al, 2014), pilot-(Jinhua et al, 2006Miura et al, 2007) and full-scale (Jo et al, 2016) MBRs.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
See 2 more Smart Citations
“…This difference was due to the difference in the assembly mechanism of AS and biofilm communities, which are two distinct forms of microbial aggregates. Similar results were reported in previous studies where the biofilm community was distinct from the AS community in lab- (Lim et al, 2004;Choi et al, 2006;Zhang et al, 2006;Huang et al, 2008;Fontanos et al, 2010;Lim et al, 2012;Piasecka et al, 2012;Lee et al, 2014), pilot-(Jinhua et al, 2006Miura et al, 2007) and full-scale (Jo et al, 2016) MBRs.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…6 Previous studies characterizing the biofilm microbial community in MBRs (Lim et al, 2004;Choi et al, 2006;Jinhua et al, 2006;Zhang et al, 2006;Miura et al, 2007;Huang et al, 2008;Fontanos et al, 2010;Lim et al, 2012;Piasecka et al, 2012;Lee et al, 2014, showed that the biofilm microbial community was distinct from the AS community. Despite these numerous studies, we still know little of the bacteria that form biofilms on membrane surfaces of MBRs.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…). The Opitutus genera have been also detected in biofilms converting nitrogenous metabolites into atmospheric nitrogen (Lee, Hong, Kim, Hong & Park ), and can use almost all of the monosaccharide exudates produced by Navicula sp. as carbon sources (Kaluzhnaya et al .…”
Section: Discussionmentioning
confidence: 99%
“…The species has been usually associated to paddy soil (Chin, Liesack & Janssen 2001), but recently to the marine environment also (Kaluzhnaya et al 2012). The Opitutus genera have been also detected in biofilms converting nitrogenous metabolites into atmospheric nitrogen (Lee, Hong, Kim, Hong & Park 2014), and can use almost all of the monosaccharide exudates produced by Navicula sp. as carbon sources (Kaluzhnaya et al 2012).…”
Section: Discussionmentioning
confidence: 99%